Attitudes towards 3R Culture in Maktab Rendah Sains Mara Mukah, Sarawak / Elissia anak Agun@Ensaring... [et.al] - Agun @ Ensaring, Elissia; Derahim, Mazuin; Ab Rahman, Rahmatul Aida (2014)
The purpose of this study is to identify the strategies in nurturing the 3R culture among the community MRSM Mukah, Sarawak. Prior to any other steps, the observation of current 3R culture has been made. Through the observation, the 3R in MRSM Mukah is still very poorly practiced by the community. Despite of that, this study also utilized survey approach to determine the level of awareness of 3R culture in MRSM Mukah. This survey was conducted by 222 respondents among the community. The survey was analysed by using the ANOVA. The results indicate that there is a higher level of awareness of 3R culture in MRSM Mukah environment, but it was not well practiced. The most factors that cause the problems were lack of information of 3R and also lack of 3R facilities such as 3R bins. Thus, in this study, researchers launched the 3R bins at 4 different locations around the college. The locations are female hostel, male hostel, academic block and Koperasi building. From the observation of the 3R bins, MRSM Mukah community starts to use the 3R bins correctly and starts to implement 3R culture in their daily routine. Due to the time limitation, the observation was conducted only for 22 days. However, the researchers convey the monitoring of the 3R bins to the college’s management. The reports of the usage and the condition of the 3R bins will be submitted every semester by Badan Wakil Pelajar. This is to ensure that the 3R culture will be continuously spreads over the MRSM Mukah community years by years and also being implemented to other school in Malaysia.